PENGARUH VARIASI LARUTAN PERENDAMAN SUKUN TERHADAP KARAKTERISTIK FISIKO KIMIA TEPUNG SUKUN - Fauzi, Andi Akhmad; Muhsin, Muhsin; Sukainah, Andi (Universitas Negeri Makassar, 2016)
This study aims to find the best soaking treatment to produce breadfruit flour. This study used a completely randomized design (CRD) with a soaking sodium chloride, sodium metabisulfite and sodium acid pyrophosphat. The parameters measured were the color, yield, kamba density, water content, starch and ash content. The results showed that the best treatment was soaking treatment with a combination of sodium chloride and sodium metabisulfite (A) with the resulting color values are 30.72%, the yield of 28.35%, Kamba density of 0.76 g / ml, water content of 9.66 %, starch content of 57.13, ash content of 3.85